Development of Employee Job Satisfaction Survey System with Access Management Based on Job Position Using Scrum Framework (Case Study: Era Medika Hospital) - Meyliana Wafaul Ummah; Yayak Kartika Sari; Agung Prasetya (Telematika, 2025)
Era Medika Hospital is a privately-owned general hospital committed to quality service and patient safety by continuously evaluating and improving various aspects, including the quality of human resources (HR) or staff, whose service quality is greatly influenced by their job satisfaction. To assess employee job satisfaction, the HR management routinely conducts a survey in the form of a questionnaire every six months using the XYZ Application. However, from experience with this application, HR management has encountered issues such as duplicate survey submissions by employees, difficulties managing questionnaire access rights based on employee positions, and manual separation of suggestion responses by category. This study aims to develop a web-based Employee Job Satisfaction Survey System at Era Medika Hospital with access management based on employee roles using the Scrum framework. The system development applies an agile Scrum approach, dividing the design, implementation, and testing phases into three sprints, each followed by sprint reviews with stakeholders. The developed system features solutions addressing the encountered problems, such as login/sign-in using employee identification numbers (NIP) to ensure each employee submits the survey only once, questionnaire data management including access control by position, and automatic categorization of suggestion responses starting from the survey input.Evaluation results indicate the system meets both functional and non-functional requirements as expected by users. Achieving the research objectives, the system is expected to operate optimally, support data-driven decision-making, and improve employee satisfaction and productivity, ultimately contributing to enhancing the quality of healthcare services provided by Era Medika Hospital.